Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1 :
a, 5/7 - 3/6 + 2/7 + 9/6 - 4/3 - 1/3
= (5/7 + 2/7) + (9/6 - 3/6) - (4/3 + 1/3)
= 1 + 1 - 5/3
= 2- 5/3
= 1/3
b. 0,75 + 5,64 + ( 7,25 - 3,14 )
= (0,75 + 7,25) + (5,64 - 3,14)
= 8 + 2,5
= 10,5
c, 15/26 x 39/25 x 54/18 x 36/27 ( Làm = cách triệt tiêu )
\(=\frac{15\cdot39\cdot54\cdot36}{26\cdot25\cdot18\cdot27}\)
\(=\frac{3\cdot5\cdot3\cdot13\cdot27\cdot2\cdot2\cdot18}{2\cdot13\cdot5\cdot5\cdot18\cdot27}\)
\(=\frac{3\cdot3\cdot2}{5}\)
\(=\frac{18}{5}\)
Bài 2 : Tìm x
a, ( 6,73 + 5,26 - 3,5 ) - x = 4,32 - 2,56
8,49 - x = 1,76
x= 8,49 - 1,76
x= 6,73
b, x : ( 7,25 - 5,42 ) = 4,63 +1,37
x : 1,83 = 6
x= 6 * 1,83
x= 10,98
a, 3/4 ÷ x/6 = 0,75
x/6 = 0,75 ÷ 0,75
x/6 = 1
=> x = 6
Vậy x = 6
b, 2,5 . 45/ x = 5/6
45/x = 5/6 ÷ 2,5
45/x = 1/3
=> x = 45 × 3
=> x = 135
Vậy x = 135
c, x/12 + 121,5 = 121,5
x/12 = 121,5 - 121,5
x/12 = 0
=> x = 0
Vậy x = 0
e, 6/8 = 15/x
3/4 = 15/x
=> x = 20
Vậy x = 20
\(a,\frac{2}{3}=\frac{x}{54}\)
\(\Rightarrow2.54=3x\)
\(\Rightarrow3x=108\)
\(\Rightarrow x=108:3=36\)
\(b,\frac{10}{x}=\frac{15}{6}\)
\(\Rightarrow10.6=15x\)
\(\Rightarrow15x=60\)
\(\Rightarrow x=60:15=4\)
\(c,\frac{2}{3}< \frac{x}{6}< 1\)
\(\Rightarrow\frac{4}{6}< \frac{x}{6}< \frac{6}{6}\)
\(\Rightarrow4< x< 6\)
\(\Rightarrow x=5\)
\(d,1< \frac{6}{x}< 2\)
\(\Rightarrow\frac{6}{6}< \frac{6}{x}< \frac{6}{3}\)
\(\Rightarrow6< x< 3\)
\(\Rightarrow x=5;4\)
a) Ta thấy \(\frac{1}{2}< \frac{2}{3};\frac{3}{4}< \frac{4}{5};...;\frac{99}{100}< \frac{100}{101}\)
\(\Rightarrow A=\frac{1}{2}.\frac{3}{4}.\frac{5}{6}...\frac{99}{100}< B=\frac{2}{3}.\frac{4}{5}.\frac{6}{7}...\frac{100}{101}\)
b) \(A.B=\left(\frac{1}{2}.\frac{3}{4}.\frac{5}{6}...\frac{99}{100}\right).\left(\frac{2}{3}.\frac{4}{5}.\frac{6}{7}...\frac{100}{101}\right)\)
\(A.B=\frac{1.\left(3.5...99\right).\left(2.4.6...100\right)}{\left(2.4.6...100\right).\left(3.5.7...99\right).101}=\frac{1}{101}\)
c) vì A < b nên A . A < A . B < \(\frac{1}{101}< \frac{1}{100}\)
do đó : A . A < \(\frac{1}{10}.\frac{1}{10}\)suy ra A < \(\frac{1}{10}\)
\(a,\frac{1}{3}+\frac{1}{6}+x=\frac{3}{4}\) \(b,\frac{1}{2}+\frac{1}{3}-x=\frac{2}{3}\) \(c,\frac{2}{3}\cdot\frac{3}{4}\cdot x=\frac{2}{5}\)
\(\left(\frac{1}{3}+\frac{1}{6}\right)+x=\frac{3}{4}\) \(\left(\frac{1}{2}+\frac{1}{3}\right)-x=\frac{2}{3}\) \(\left(\frac{2}{3}\cdot\frac{3}{4}\right)\cdot x=\frac{2}{5}\)
\(\frac{1}{2}+x=\frac{3}{4}\) \(\frac{5}{6}-x=\frac{2}{3}\) \(\frac{1}{2}\cdot x=\frac{2}{5}\)
\(x=\frac{3}{4}-\frac{1}{2}\) \(x=\frac{5}{6}-\frac{2}{3}\) \(x=\frac{2}{5}:\frac{1}{2}\)
\(x=\frac{1}{4}\) \(x=\frac{1}{6}\) \(x=\frac{4}{5}\)
\(d,x:\left(\frac{1}{4}:\frac{1}{2}\right)=\frac{2}{3}\) \(e,\frac{1}{3}:\frac{1}{2}:x=\frac{3}{4}\)
\(x:\frac{1}{2}=\frac{2}{3}\) \(\frac{1}{3}:\frac{1}{2}=\frac{3}{4}\cdot x\)
\(x=\frac{2}{3}\cdot\frac{1}{2}\) \(\frac{2}{3}=\frac{3}{4}\cdot x\)
\(x=\frac{1}{3}\) \(x=\frac{2}{3}:\frac{3}{4}\)
\(x=\frac{8}{9}\)
a) 1/3 + 1/6 +x = 3/4 b) 1/2 + 1/3 - x = 2/3
5/6 - x = 2/3
x =5/6 -2/3
x = 1/6
1/2+ x =3/4
x = 3/4 -1/2
x = 1/4